Application of FDEM in the study of large deformation mechanisms in deep-buried soft rock tunnels: A case study - Wang, Yanning; Qiao, Jiangang; Zheng, Shaohua; He, Zhiwei; Hu, Yongkang; Yan, Chengzeng (Frontiers in Earth Science, 2024)
The Hutou Beishan Mega Tunnel frequently experiences significant deformation and instability collapse when passing through weak and fractured rock strata, leading to frequent design modifications and adversely impacting the construction progress and costs. This paper employs the finite-discrete element method (FDEM) to investigate the mechanisms and characteristics of large deformations in soft rock and analyzes the effects of in-situ stress and lateral pressure coefficients on the stability of soft rock tunnels. The results indicate that: (1) Once the compressive stress concentration exceeds the shear strength of the surrounding rock, shear failure occurs, with the resulting cracks predominantly forming X-shaped conjugate fractures. The shape of the excavation damage zone (EDZ) corresponds to the stress state; (2) Under hydrostatic stress conditions, the extent of damage to weak surrounding rock is influenced by the in-situ stress. At lower in-situ stress levels, only a few cracks appear at the edges of the surrounding rock, and deformation is minimal. At higher in-situ stress levels, cracks extend deeper into the tunnel, crushing shallow rock; (3) The failure characteristics of the tunnel vary with different lateral pressure coefficients. As the lateral pressure coefficient changes, the shape of the EDZ also changes, and the concentrated damage zone shifts from the arch waist to the crown as the lateral pressure coefficient increases.